Distribution and population structure of the anther smut Microbotryum silenes‐acaulis parasitizing an arctic–alpine plant. Issue 3 (February 2016) - Bueker, Britta; Eberlein, Chris; Gladieux, Pierre; Schaefer, Angela; Snirc, Alodie; Bennett, Dominic J.; Begerow, Dominik; Hood, Michael E.; Giraud, Tatiana
Abstract: Cold‐adapted organisms with current arctic–alpine distributions have persisted during the last glaciation in multiple ice‐free refugia, leaving footprints in their population structure that contrast with temperate plants and animals. However, pathogens that live within hosts having arctic–alpine distributions have been little studied. Here, we therefore investigated the geographical range and population structure of a fungus parasitizing an arctic–alpine plant. A total of 1437 herbarium specimens of the plant Silene acaulis were examined, and the anther smut pathogen Microbotryum silenes‐acaulis was present throughout the host's geographical range. There was significantly greater incidence of anther smut disease in more northern latitudes and where the host locations were less dense, indicating a major influence of environmental factors and/or host demographic structure on the pathogen distribution. Genetic analyses with seven microsatellite markers on recent collections of 195 M. silenes‐acaulis individuals revealed three main genetic clusters, in North America, northern Europe and southern Europe, likely corresponding to differentiation in distinct refugia during the last glaciation. The lower genetic diversity in northern Europe indicates postglacial recolonization northwards from southern refugia. This study combining herbarium surveys and population genetics thus uniquely reveals the effects of climate and environmental factors on a plant pathogen species with an arctic–alpine distribution.